Self-control and savings - Philippe Michel; Jean-Pierre Vidal (European Central Bank (ECB), 2003)
We reconsider the well-established paradigm of a rational individual's choice of a consumption schedule, building on the idea that human beings devote resources to withstand their desire for immediate consumption, i.e. to become more patient, thereby making less remote the pleasure derived from deferred consumption. We construct an infinite-horizon model of a small open economy, in which individuals can accumulate a stock of personal capital that reduces the discount on future consumption. Personal capital captures the effect of a conumer's past experience and choices on his future utilities. Our main results are: i) when individuals are heterogenous with respect to ability to become patient all individuals exhibit the same rate of time preference in the long run; ii) effort is rewarded in the long run to the extent that individuals who need to make more effort to become patient are wealthier and enjoy a higher level of utility bin the steady state. The latter result stems from the complementarity between personal capital and deferred consumption.
Keywords: E13; 330